Transformational Islamic Leadership and Religious School Culture: An Interpretative Phenomenological Study in General Islamic Schools - Hafizh Taufiq Fadlur Rahman; Ice Rosina Sari; Betty Anggoro Weni; Nirva Diana; Eti Hadiati (ISTAWA, 2026)
This study examines the meaning and practice of transformational Islamic leadership in strengthening religious school culture at SMA Al-Azhar 3 Bandar Lampung. Grounded in the premise that religious culture is not merely a set of ritual activities but a lived system of values shaping moral consciousness, this research adopts an interpretative phenomenological approach to explore how leadership practices are experienced and internalized by school actors. Data were collected through in-depth interviews, participatory observations, and document analysis involving the principal, vice principals, religious guidance teachers, and students. The findings reveal that transformational Islamic leadership operates through three interrelated mechanisms: spiritual role modeling that establishes moral legitimacy, empathetic and persuasive communication that fosters reflective moral awareness, and institutional policies that embed Islamic values into daily school routines. The study demonstrates that religious culture is constructed not through formal regulation alone, but through lived experiences, consistent moral example, and value-based institutional structures. Penelitian ini mengkaji makna dan praktik kepemimpinan Islam transformatif dalam memperkuat budaya keagamaan sekolah di SMA Al-Azhar 3 Bandar Lampung. Berangkat dari pandangan bahwa budaya keagamaan tidak sekadar merupakan rangkaian aktivitas ritual, melainkan sistem nilai yang hidup dan membentuk kesadaran moral, penelitian ini menggunakan pendekatan fenomenologi interpretatif untuk mengeksplorasi bagaimana praktik kepemimpinan dialami dan diinternalisasi oleh warga sekolah. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen yang melibatkan kepala sekolah, wakil kepala sekolah, guru pembina keagamaan, dan peserta didik. Hasil penelitian menunjukkan bahwa kepemimpinan Islam transformatif beroperasi melalui tiga mekanisme yang saling terkait, yaitu keteladanan spiritual yang membangun legitimasi moral, komunikasi empatik dan persuasif yang menumbuhkan kesadaran moral reflektif, serta kebijakan institusional yang mengintegrasikan nilai-nilai Islam ke dalam rutinitas sekolah sehari-hari. Penelitian ini menegaskan bahwa budaya keagamaan terbentuk bukan semata-mata melalui regulasi formal, melainkan melalui pengalaman hidup, keteladanan moral yang konsisten, dan struktur kelembagaan berbasis nilai.